Derrida's Bible
XV, 323 p.
Keywords: In the last few years, Derrida has gained a great deal of attention from scholars of biblical studies and theology. The contributors to Derrida's Bible explore the relationships between Derrida, theory, and religious studies. Unlike other books on Derrida, this collection is primarily focused on biblical studies, where others are concerned with Derrida and religion in general.